Meshing Theory Analysis of Parallel Inclined Double Roller Enveloping Hourglass Worm Drive - Honghui Liao; Xudong Wang; Yan Qi; Zaixin Liu (Jixie chuandong)
Based on the modification of single roller enveloping hourglass worm drive， a new type of worm drive， parallel inclined double roller enveloping hourglass worm drive is proposed. According to the principle of single roller enveloping worm drive and spatial meshing theory， the basic mathematical model of parallel inclined double roller enveloping hourglass worm drive is constructed. Based on the established mathematical model， the basic characteristic parameters of the new type worm drive， such as induced normal curvature， lubrication angle， self-rotation angle， meshing equation and tooth surface equation are analyzed and deduced. According to the obtained basic characteristic parameters， the meshing performance of the new worm drive is analyzed. The analysis results show that this new type of worm drive has good meshing performance.